Comunicata Scientiae: a horticulture journal - Cavalcante, Ítalo Herbert Lucena (Comunicata Scientiae, 2019)
Comunicata Scientiae is a scientific journal created at the Campus "Prof.a Cinobelina Elvas" of the Federal University of Piauí in 2009, which had the first issue published in 2010. Initially, the journal aimed to disseminate the knowledge generated by the scientific community through the publication of research results and new scientific proposals unpublished and relevant to the Agrarian and Environmental Sciences. With this proposal, the journal had a significant growth in the proposed knowledge areas (Agrarian and Environmental Sciences) and it was indexed in the main databases of the world as SCOPUS (Elsevier), obtaining SJR already in 2011 of 0,187, a value that is currently 0.372, which includes it in the second best category of SCOPUS, the Q2...